Relationship between food triggers and sensory hypersensitivity in patients with migraine - Vitali-Silva, Aline; Bello, Valéria Aparecida; Poli-Frederico, Regina Célia; Oliveira, Carlos Eduardo Coral de; Reiche, Edna Maria Vissoci; Bossa, Beatriz Bagatim; Rezende, Debora Villas Boas; Khouri, Bárbara Ferreira; Silva-Néto, Raimundo Pereira (Arquivos de Neuro-Psiquiatria, 2024)
Background The recognition of food as the trigger of attacks occurs in approximately 25% of individuals with migraine. However, differentiating migraine food triggers and prodrome symptoms is still a challenge.Objective To understand the association of clinical characteristics of migraine with food triggers and to identify predictors of food triggers.Methods Patients with migraine diagnosed according to the criteria of the third edition of the International Classification of Headache Disorders (ICHD-3) were evaluated for the presence or absence of food triggers.Results In total, 502 patients with migraine were investigated, and they were divided into two groups: those with food triggers (58.4%) and those without food triggers (41.6%). The main food triggers were alcohol (44%), chocolate (42%), cheese (27.7%), excess carbohydrates (27.7%), coffee (21.8%), cold cuts (16%), and citrus fruits (11.9%). Aura and excessive use of analgesics were more frequent among patients with food triggers (p = 0.022). Photophobia and osmophobia were associated with the presence of a food trigger (p < 0.001). There was a greater impact of migraine in the presence of food triggers (p = 0.002). Through binary logistic regression, we identified clinical predictors of food triggers, such as photophobia and osmophobia.Conclusion The presence of a food trigger was significantly associated with photophobia and osmophobia. Osmophobia might be another mechanism by which patients perceive foods as triggers for their migraine attacks.
Keywords: Migraine Disorders; Photophobia; Hyperacusis; Olfaction Disorders; Precipitating Factors; Food; Sensation Disorders